5. EVALUASI KERJASAMA UNODC DAN PEMERINTAH INDONESIA DALAM MENGATASI PERDAGANGAN NARKOBA JENIS CRYSTALLINE METHAMPHETAMINE DI INDONESIA (2007-2013) - Putra, Adhimukti Parama; Windiani, Reni; P, Shary Charlotte (Journal of International Relations, 2016)
Crystalline methamphetamine, also known in Indonesia as sabu, is a kind of illegal drugthat is currently getting high demand in Indonesia. Based on the information from BNNand UNODC the number of drug use and trafficking of crystalline methamphetamine inIndonesia is really high. Indonesia in this position really need UNODC recommendationsto overcome this new kind of drug. Based on the background, this research’s purpose is toshow how Indonesian Government's implementing partnership with UNODC against illicitdrug trafficking crystalline methamphetamine in Indonesia in 2007-2013. If we look at thetheme and the topic, The purpose of this research is to evaluate the process of cooperationbetween the Indonesian government and UNODC against drug trafficking of crystallinemethamphetamine in Indonesia from 2007 to 2013. Cooperation between the two sides hasbeen running well if we see the increasing number of arrested person which wassuccessfully carried out by Indonesian law enforcement in 2007-2013. crystallinemethamphetamine crime still exist in Indonesia nowadays, though due to several factors,such as the type of the drug itself that is easy to manufacture and materials that can bereplaced with other materials and tools manufacture that can be easily found, place-makingwhich can be done in a small laboratory, a geographical location of Indonesia, and thecontrol problem of the Indonesian law enforcement.